Analysis of errors according to Newman in solving the spherical triangle - Ari Sriantini; Mochamad Cholik (Math Didactic: Jurnal Pendidikan Matematika, 2021)
The purpose of this descriptive study with qualitative approach was identifying the types of errors, the causes of errors, and how to correct them. According to Newman, these types of errors include reading, comprehension, shifting, processing, and numerical errors. The research subjects in this study were 25 students who use the test, interview, and writing methods from the first phase of the water research program. The results of the results of the interview and the student’s answers to the test were tested. The paperwork method is uses to determine the names of the students to be studied. Bases on the results of the study, 23,6% of reading error, 21,8% of reading comprehension difficulty, 17,3% of transform error, 26,4% of students experienced error in the process skill stage, 10,9% of students experience errors at the notation stage. These errors are caused by a lack of understanding of the questions given, the students are not able to change questions in the form of stories into mathematical sentences, are not careful, lack practice in working on story problems, and forget about the formulas. Lecturers should often introduce problems spherical triangle contextual to the student to improve student understanding, the student must often be trained to work on matters story that relates to the spherical triangle with various variations to practice accuracy and skills.